Kembalinya WNI Eks Islamic State of Iraq and Syria (ISIS): Sebuah Langkah Yang Dapat Mempengaruhi Kasus Terorisme di Indonesia - Edi Saputra Hasibuan (KRTHA BHAYANGKARA, 2022)
The storm of the threat of terrorism is still lurking and cannot be just a figment, this article aims to highlight what became a hot issue in the middle of 2019-2020. Yes, the discourse on the return of sympathizers or supporters of the Islamic State of Iraq and Syria (ISIS) movement for those who come from Indonesia or have Indonesian citizenship status, so that they can return to their homeland. It is ironic to remember that many people go and become sympathizers with the belief that they have chosen the right path, but in fact they still need the attention of their homeland. Apart from the pros and cons of the repatriation of ex-ISIS, the author would like to highlight how the issue of repatriation is actually a complex matter, a one-day decision will have an impact on many things, including terrorism cases that will increase in the future, then whether the discourse on terrorism will increase in the future. The repatriation is appropriate because it pays attention to human rights and is the responsibility of the Indonesian side for the behavior of its citizens in other countries or it becomes a potential threat to the welfare and security of the country itself.